Military leader of representatives of the national independence movement as lines to the personality (Eurasian Research Bulletin, 2023)
The reason that prepared the ground for the beginning of the independence movement, the difference between " robbers" and the struggle for national liberation is explained. The socio-political situation of the commanders in the process of their appearance on the stage of history, the role of the commanders as military commanders, and the psychological effects that they used in the movement of the army under their command against the enemy were touched upon. . Achievements and shortcomings of the representatives of the independence movement, their activities are approached from a historical-military point of view.